Salvation in the Gospel of Mark the death of Jesus and the path of discipleship - Markusse-Overduin, Gabrielle; Middleton, Paul (Eugene, Oregon Pickwick Publications, 2018)
Introduction -- Implications of Mark's narrative structure -- The (im)possible path of discipleship -- The noble death and the emotions of Jesus -- The divine pathos -- Mark and martyrdom -- Mark's use of Isaiah's salvation narrative -- Mark's use of Daniel's One like a son of man -- Mark's use of Psalm 22's righteous sufferer -- Conclusions.
Revision of author's thesis (Ph. D.)--University of Manchester, 2013
Includes bibliographical references (pages 181-194) and index
Keywords: Jesus Christ -- Crucifixion -- History of doctrines -- Early church, ca. 30-600; Bible -- Criticism, interpretation, etc; Bible -- Theology; Christian Life -- Biblical teaching; Salvation -- Biblical teaching; Jesus Christ; Bible; Christian life ; Biblical teaching; Crucifixion ; History of doctrines; Salvation ; Biblical teaching; Theology; Criticism, interpretation, etc